Combining theoretical potential and advanced technology in high-dose rate brachytherapy boost therapy for prostate cancer. (November 2013) - Zaorsky, Nicholas G; Den, Robert B; Doyle, Laura A; Dicker, Adam P; Hurwitz, Mark D
External beam radiation therapy (EBRT) combined with brachytherapy (BT) is an attractive treatment option for select patients with clinically localized prostate cancer. Either low- or high-dose rate BT may be combined with EBRT ('LDR-BT boost, ' 'HDR-BT boost, ' respectively). HDR-BT boost has potential theoretical benefits over LDR-BT boost or external beam radiation therapy monotherapy in terms of radiobiology, radiophysics and patient convenience. Based on prospective studies in this review, freedom from biochemical failure (FFBF) rates at 5 years for low-, intermediate- and high-risk patients have generally been 85–100%, 68–97%, 63–85%, respectively; late Radiotherapy and Oncology Group Grades 3 and 4 genitourinary and gastrointestinal toxicities are seen in <8% of patients. HDR-BT boost is now a relatively well-established treatment modality for certain intermediate-risk and high-risk prostate cancer patients, though limitations exist in drawing conclusions from the currently published studies.